Analyzing Predator-Prey Model - Kunwar, Laxman Bahadur (Mathematics Education Forum Chitwan, 2019)
In this article, we consider a system involving two-species living in the same environment and describe the model for their population growth presented by Lotka and Volterra. The model is the foundation for the development of many other models. The model is known as Predator-Prey Model or Lotka-Volterra system. In more modern theories, there will be multiple species each with their own interactions but we will limit ourselves to this simpler but highly instructive classical system. We shall cover various standard tools for analysing such systems. We shall discuss dynamic solutions, equilibrium solutions and phase curves that best illustrate the phenomena.